Webometric Analysis of Websites of Autonomous Colleges Under Mahatma Gandhi University, Kottayam: A Study - George, Agie Elizabeth; Mohanan, Neethu (Information Research Communications, 2024)
The World Wide Web, also known as the Web, is a technologically breakthrough creation. In recent years, web traffic has expanded exponentially due to the rising use of websites as conduits for interpersonal contact. Utilising metrics, it is possible to estimate the number of people connected to the internet and the material they share and find engaging. The websites of educational institutions can disseminate a wide variety of information to the user community through the development and maintenance of attractive and well-designed institutional websites. Developing standards for designing educational institutions’ websites is a basic necessity. A quality institution’s website provides implicit instruction and conveys essential images of the institution. The current study is a novel attempt to explore the websites of selected autonomous colleges under Mahatma Gandhi University and to assess those websites based on various webometric indicators. The result of the study will help in self-assessment of the functioning of college websites to re-frame, re-restructure and learn from the competitors’ website.
Keywords: Autonomous Colleges; NAAC; Webometrics; Web Impact Factor; Link Analysis